Digital scenography : 30 years of experimentation and innovation in performance and interactive media - O'Dwyer, Neill (Performance and design, 2021)
"This book uses digital media theory to explore contemporary understandings of expanded scenography as spatial practice. It surveys and analyses a selection of ground-breaking, experimental digital media performances that comprise a genealogy spanning the last 30 years, in order to show how the arrival of digital technologies have profoundly transformed performance practice. Performances are selected based on their ability to elicit the unique specificities of digital media in new and original ways, thereby exposing both the richness and shortcomings of digital culture. O'Dwyer argues that contemporary scenography is largely propelled by and dependent on digital technologies and represents a rich, fertile domain, where unbridled creativity can explore new techniques and challenge the limits of knowledge. The 30-year genealogy includes works by Troika Ranch, Stelarc, Klaus Obermaier, Chunky Moves, Onion Lab and Blast Theory. In addition to applying a broad scope of performance analysis and aesthetic theory, the work includes artists' interviews and opinions. The volume opens important aesthetic, philosophical and socio-political themes in order to highlight the impact of digital technologies on scenographic practice and the blossoming of experimental interdisciplinarity. Ultimately, the book is an exploration of how evolutionary leaps in technology contribute to how humans think, act, make work, engage one another, and therefore construct meaning and identity"--